Corporate Governance and Financial Ratios of Manufacturing Companies on Financial Distress: The Main Board and Development Board of IDX - Dea Adielyani; Irene Rini Demi Pangestuti (Media Ekonomi dan Manajemen, 2023)
Financial distress is a condition where a company is unable to meet its obligations when they directed to bankruptcy. The purpose of this study was to analyze influence of corporate governance, profitability, liquidity, leverage and earning growth on financial distress. Research sample data used in this study were manufacturing companies listed on the main board and development board on the Indonesia Stock Exchange in 2016-2020. Logistic regression analysis had been applied to analyze data of study. The results show that the factors that influence Financial Distress in manufacturing companies on the main board and development board were different. For manufacturing companies on main board, influencing factors of financial distress were independent audit committee, liquidity, leverage, and earning growth. Meanwhile, board size, profitability, liquidity, leverage and earning growth were influencing factors of financial distress for manufacturing companies on development board.